Investigation on acoustic, thermal, and tribological properties of hydrodynamic journal bearing with heterogeneous rough/smooth surface - Tauviqirrahman, Mohammad; Yohana, Eflita; Paryanto; Jamari; Muslim, Fauzan Syukri; Anggoro, Paulus Wisnu (Results in Engineering, 2023)
High level of noise limits the reliability of the lubricated journal bearing. In the current paper, the possibility of bearing design with a heterogeneous rough/smooth surface is explored using the computational fluid dynamics (CFD) approach to improve tribological and acoustic performance. A parametric analysis is conducted to determine the optimal surface roughness level, the cavitation pressure, and the ratio of length to the diameter of the journal. The effect of the presence of a roughened pattern on the thermal behavior of the lubricant, friction force, noise level, and cavitation phenomena was also studied in depth. The main finding of the present study is that when conventional journal bearing fails in generating the load support for concentric conditions, the heterogeneous rough/smooth bearing has a beneficial effect by increasing the load-carrying capacity. Furthermore, the high level of surface roughness can significantly increase the load-carrying capacity while decreasing frictional forces and acoustic power. However, the roughness does not dramatically change the maximum temperature (less than 1%). The numerical results also suggest that the variation in vapor saturation pressure has a negligible effect on the maximum temperature, friction force, and noise level.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Acoustic; Cavitation; Computational fluid dynamics (CFD); Surface roughness; Thermohydrodynamic